2014
DOI: 10.1007/s13187-014-0775-y
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up Care Education and Information: Identifying Cancer Survivors in Need of More Guidance

Abstract: Background Cancer survivors engage in cancer screenings and protective health behaviors at suboptimal rates despite their increased risk for future illness. Survivorship care plans and other educational strategies to prepare cancer survivors to adopt engaged roles in managing long-term follow-up care and health risks are needed. In a sample of cancer survivors, we identified patient characteristics and psychosocial predictors associated with increased follow-up care informational needs. Methods Cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 20 publications
4
41
0
Order By: Relevance
“…The American Society of Clinical Oncology’s (ASCO) breast cancer survivorship care plan in use at the time of the study was viewed as too technical and lacked detailed information on side effects and self-care [14]. Other research with minority breast cancer survivors reports that SCP templates are too generic [13,14,28]. In a focus group study where male and female cancer survivors reviewed an SCP template for colorectal cancer, Hewitt et al reported that participants preferred SCPs that were more personalized, tailoring the treatment plan to the individual, and were written in layman’s terms [28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The American Society of Clinical Oncology’s (ASCO) breast cancer survivorship care plan in use at the time of the study was viewed as too technical and lacked detailed information on side effects and self-care [14]. Other research with minority breast cancer survivors reports that SCP templates are too generic [13,14,28]. In a focus group study where male and female cancer survivors reviewed an SCP template for colorectal cancer, Hewitt et al reported that participants preferred SCPs that were more personalized, tailoring the treatment plan to the individual, and were written in layman’s terms [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cancer survivors have expressed enthusiastic support for SCPs [28,29]. However, the promise of an SCP as a quality improvement tool is dependent in large part on system level issues [13,14]. Oncologists often do not have the time to create individualized SCPs or to discuss the content with their patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Minority ethnic groups that do search for health information are more likely to specifically seek support service information and psychosocial support compared with non-Hispanic whites [37, 71]. A recent cross-sectional survey of breast and prostate cancer survivors (>2 years post-treatment) showed that African Americans reported greater informational needs compared with other races [76]. The National Cancer Institute's 2003 HINTS Survey similarly found that cancer information seekers were younger, female, had higher income, and a regular health care provider [73].…”
Section: Discussionmentioning
confidence: 99%